Pengaruh Strategi Numbered Heads Together (Nht) Dan The Power Of Two Terhadap Hasil Belajar Matematika Ditinjau Dari Motivasi Belajar Siswa Kelas Viii Mts Negeri Surakarta 1 Tahun Ajaran 2015/2016 - Budi Pratiwi, Alifah (2016)
This research aims to understanding: (1) the effect of mathematics learning outcomes by using NHT and The Power of Two, (2) the effect of the mathematics learning outcomesviewed from students learning motivation,(3) the interaction between learning strategy and students' motivation toward mathematic learning outcomes. The type of the research is an experiment research with quasiexperimental design. The population ofthe research was all students of odd semester of class VIII of MTs Surakarta 1 in 2015/2016 academic year. Sample of this research consist of two classes. The sampling technique istakenby using cluster random sampling. Methods of data collection are taken byusingdocumentation, questionnaire and test. Technique of data analysis by using analysis of variance withtwo different cell lines. The results of data analysis with significance level of 5% was obtined: (1) there is effect of NHT strategies and The Power of Two on the outcomes of students' mathematics learning with = 4.424 (2) there is effect of learning motivation for the mathematics learning outcomes of students with = 11.487, (3) there is no interaction between learning strategic and student learning motivation toward mathematics learning outcomes of students with = 0.018.